Differential Tunneling‐Driven and Vibrationally‐Induced Reactivity in Isomeric Benzazirines. Issue 67 (13th October 2022) - Nunes, Cláudio M.; Doddipatla, Srinivas; Loureiro, Gonçalo F.; Roque, José P. L.; Pereira, Nelson A. M.; Pinho e Melo, Teresa M. V. D.; Fausto, Rui
Abstract: Quantum mechanical tunneling of heavy‐atoms and vibrational excitation chemistry are unconventional and scarcely explored types of reactivity. Once fully understood, they might bring new avenues to conduct chemical transformations, providing access to a new world of molecules or ways of exquisite reaction control. In this context, we present here the discovery of two isomeric benzazirines exhibiting differential tunneling‐driven and vibrationally‐induced reactivity, which constitute exceptional results for probing into the nature of these phenomena. The isomeric 6‐fluoro‐ and 2‐fluoro‐4‐hydroxy‐2 H ‐benzazirines (3‐a and 3′‐s ) were generated in cryogenic krypton matrices by visible‐light irradiation of the corresponding triplet nitrene 3 2‐a, which was produced by UV‐light irradiation of its azide precursor. The 3′‐s was found to be stable under matrix dark conditions, whereas 3‐a spontaneously rearranges ( τ 1/2 ∼64 h at 10 and 20 K) by heavy‐atom tunneling to 3 2‐a . Near‐IR‐light irradiation at the first OH stretching overtone frequencies (remote vibrational antenna) of the benzazirines induces the 3′‐s ring‐expansion reaction to a seven‐member cyclic ketenimine, but the 3‐a undergoes 2 H ‐azirine ring‐opening reaction to triplet nitrene 3 2‐a . Computations demonstrate that 3‐a and 3′‐s have distinct reaction energy profiles, which explain the different experimental results. The spectroscopic direct measurement of the tunneling of 3‐a to 3 2‐a constitutes a unique example of an observation of a species reacting only by nitrogen tunneling. Moreover, the vibrationally‐induced sole activation of the most favorable bond‐breaking/bond‐forming pathway available for 3‐a and 3′‐s provides pioneer results regarding the selective nature of such processes. Abstract : Quantum tunneling and IR vibrational excitation chemistry was discovered to manifest differently in two isomeric benzazirines generated in cryogenic matrices. Computations show that these reactive intermediates have distinct energy profiles regarding two competitive bond‐breaking/bond‐forming pathways. These exceptional results allow probing into the fundamental nature of such unconventional types of chemical reactivity.